(untitled) (Al-Mansour Journal, 2022)
In the last few years, the demand for mobile communication services has increased tremendously. However, there is no proportionate increase in the spectrum allocated. As a result, there is an urgent need for new techniques to improve system spectral efficiency, therefore maximizing the capacity of cellular system. SDMA (Space Division Multiple Access) integrated with CDMA (Code Division Multiple Access), resulting a system which combines between the robustness against Multiple Access Interference (MAI) of the SDMA and the multiuser capability of CDMA which is reflected on the performance of the SDMA-CDMA system. In this paper the BER performance of asynchronous (Uplink) CDMA mobile cellular system was simulated, taking into account Rayleigh fading channel, convolutional encoder, Viterbi decoder, and Rake Receiver. Simulation results was agreed with theoretical results for different, system parameters such as number of users, spreading factors, number of multipath, Rake fingers, adjacent interfering cells, , and coding ratio. When antenna directivity was introduced, results shows that the SDMA-CDMA system has a significant performance improvement over that of a conventional CDMA system.